PENGARUH PENDAPATAN DAN PEMBELIAN ASSET TERHADAP PELAPORAN PAJAK ORANG PRIBADI BERBASIS SISTEM KOMPARASI PADA MITRA KERJA PT ABC - Astuti, Yuni; Munandar, Agus (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The purpose of this study is to determine the influence of income and asset purchases on individual tax reporting using a comparative system carried out on the scope of PT ABC's partners. This study uses quantitative descriptive methods in the form of observations, interviews and case studies on tax reporting documentation. Based on the results of observations and interviews, many respondents do not know the influence of income and asset purchases on personal tax reporting, so many of the respondents are unable to explain questions from the tax office regarding income that is not propotional to asset purchases. The results of the study show that the comparative system implemented by PT ABC in handling personal tax reporting is very effective and able to minimize these problems.